Iron-Promoted Construction of Indoles via Intramolecular Oxidative C–N Coupling of 2-Alkenylanilines Using Persulfate - Wang, Menglan; Li, Yudong; Wu, Qing-An; Luo, Shuping; Li, Yuehui (Synthesis, 2019)
Indole scaffold synthesis relies primarily on oxidative C–H amination of N-protected alkenylanilines for C–N intramolecular cyclization reactions. Herein, for the first time, without N-protection, various readily prepared 2-alkenylanilines were transformed into the desired indole products in good yields by using K2S2O8 as oxidant in the presence of catalytic amounts of FeF2. The K2S2O8/FeF2 system offers a direct and benign synthetic route to 3-arylindoles and it is applicable to a wide range of substituted indoles including drug intermediates.
Keywords: indoles; C–N coupling; 2-alkenylanilines; oxidative amination; iron catalysis; 3-arylindoles; unprotected anilines